Two Meetings with Grigol Robakidze and Kita Chkhenkeli: (გრიგოლ რობაქიძესა და კიტა ჩხენკელთან) - Rusudan Enukidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
The article deals with hitherto unknown details of the author’s meeting in Geneva and Lausanne in 1961 with two eminent Georgian figures: Grigol Robakidze and Kita Chkhenkeli.